PERJANJIAN ALIH DEBITUR YANG DIBUAT DIBAWAH TANGAN BERDASARKAN KETENTUAN PASAL 37 PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - S. Birih, Andreas Sugara (Jurisdictie: Jurnal Hukum dan Syariah, 2018)
This research aims to review and analyze the implication of over credit agreement made personally in the perspective of Government Regulation Section 37 Number 24 Year 1997 regarding Land Registration. This is a juridical normative using legislation and conceptual approaches. Legislation approach is used to analyze problem and relate it with the regulation of over credit. by relating to the provisions of the laws and regulations relating to the implementation of agreement for the transfer of debtor liabilities. Conceptual approach is used to review over credit agreement as a habitual concept in the society. The result shows that private agreement on over credit is invalid because it is against the good will principle which become one of requirements in an agreement ruled in the section 1320 of Civil Code.